2013
DOI: 10.1007/s10071-013-0707-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantity estimation and comparison in western lowland gorillas (Gorilla gorilla gorilla)

Abstract: We investigated the quantity judgment abilities of two adult male western lowland gorillas (Gorilla gorilla gorilla) by presenting discrimination tasks on a touch-screen computer. Both gorillas chose the larger quantity of two arrays of dot stimuli. On some trials, the relative number of dots was congruent with the relative total area of the two arrays. On other trials, number of dots was incongruent with area. The gorillas were first tested with static dots, then with dots that moved within the arrays, and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Although new technologies are constantly in development, most contemporary touchscreen systems in use in zoological settings are classified as capacitive, resistive, or infrared. Capacitive touchscreens (e.g., Vonk et al, ) function by sensing the conductive properties of a touching finger and determining the location of the touch based on a change in the screen's electrical field (Lancet, ). Such systems are extremely accurate but because they rely on the electrical charge, they often fail to record touches made by apes, who have thicker skin, and by birds’ beaks, which has resulted in some difficulties with transmission (Lee, ).…”
Section: Logistical Considerations Of Zoo‐based Touchscreen Researchmentioning
confidence: 99%
“…Although new technologies are constantly in development, most contemporary touchscreen systems in use in zoological settings are classified as capacitive, resistive, or infrared. Capacitive touchscreens (e.g., Vonk et al, ) function by sensing the conductive properties of a touching finger and determining the location of the touch based on a change in the screen's electrical field (Lancet, ). Such systems are extremely accurate but because they rely on the electrical charge, they often fail to record touches made by apes, who have thicker skin, and by birds’ beaks, which has resulted in some difficulties with transmission (Lee, ).…”
Section: Logistical Considerations Of Zoo‐based Touchscreen Researchmentioning
confidence: 99%
“…One major limitation of our study is that we did not do numerosity pre-testing, so it is also possible that gorillas and drills had more difficulty distinguishing the reward payoffs between the two options (i.e., 1 vs. 2) than did the orangutans. However, we think this is unlikely for the gorillas, who have previously demonstrated that they are perfectly capable of quantity judgments, including some of the specific subjects in our current study, who were previously tested for quantity discrimination at Zoo Atlanta (Anderson et al, 2005;Hanus & Call, 2007; for similar results using nonfood stimuli, see Paxton Gazes et al, 2017;Vonk et al, 2014). We know of no similar task in drills, although baboons, a closely related species, also discriminate quantities successfully, especially when the options are presented simultaneously (compared to sequentially), as was done in the current study (Barnard et al, 2013;Schmitt & Fischer, 2011;Smith et al, 2003).…”
Section: Discussionmentioning
confidence: 74%
“…Gorillas were separated into individual holding areas prior to data collection. These gorillas had previously been trained to use the touch screen for other studies ( McGuire & Vonk, 2018 ; McGuire et al, 2017 ; McGuire, Vonk & Johnson-Ulrich, 2017 ; Vonk et al, 2014 ). Training and testing with these animals was approved by the IACUC of Oakland University (12063-R1-A1), and the activities were presented as a form of cognitive enrichment in addition to serving to assess affect.…”
Section: Experiments Onementioning
confidence: 99%